Scenario Planning Analysis for Startup Business Case Study: Kemilau Indonesia Magazine - Mulyanto, Frieta Miasari; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2013)
This research explained about the application of scenario planning analysis as solution for Kemilau Indonesia Magazine (KIM) which was born from the opportunities as information and promotion media of tourism. As a new player, KIM has several internal and external issues that impact on its survival. The technique used in this method is to collect data and information to be analyzed in order to generate predictions as a preparation for decision making process. This method give an overview of early warning, implications and options in each scenario drawn from the analysis of external and internal as recommendation for the company which could be used as a reference in determining and developing companyâ€™s business strategy.Â Keywords: Kemilau Indonesia Magazine, scenario planning, strategic decision making, tourism magazine industryÂ